Venom characterization of the three species of Ophryacus and proteomic profiling of O. sphenophrys unveils Sphenotoxin, a novel Crotoxin-like heterodimeric β-neurotoxin - Neri Castro, Edgar (2019)
Venoms of the three species of Ophryacus (O. sphenophrys, O. smaragdinus, and O. undulatus), a viperid genus endemic to Mexico, were analyzed for the first time in the present work. The three venoms lacked procoagulant activity on human plasma, but induced hemorrhage and were highly lethal to mice. These venoms also displayed proteolytic and phospholipase A2 activities in vitro. The venom of O. sphenophrys was the most lethal and caused hind-limb paralysis in mice. Proteomic profiling of O. sphenophrys venom showed a predominance of metalloproteinase (34.9%), phospholipase A2 (24.8%) and serine protease (17.1%) in its composition. Strikingly, within its PLA2 components, 12.9% corresponded to a Crotoxin-like heterodimer, here named Sphenotoxin, which was not found in the other two species of Ophryacus. Sphenotoxin, like Crotoxin, is composed of non-covalently bound A and B subunits. Partial amino acid sequence was obtained for Sphenotoxin B and was similar (78–89%) to other subunits described. The mouse i.v. LD50 of Sphenotoxin at 1:1M radio was 0.16 μg/g. Also, like Crotoxin, Sphenotoxin induced a potent neuromuscular blockade in the phrenic nerve-diaphragm preparation. Ophryacus is the fifth genus and O. sphenophrys the third non-rattlesnake species shown to contain a novel Crotoxin-like heterodimeric β-neurotoxin. Biological significance: Ophryacus is an endemic genus of semi-arboreal pitvipers from Mexico that includes three species with restricted distributions. Little is known about the natural history of these species and nothing is known about the properties of their venoms. Research on these species' venoms could generate relevant information regarding venom composition of Mexican pitvipers. Additionally, research into the presence of neurotoxic Crotoxin-like molecules outside of rattlesnakes (genera Crotalus and Sistrurus) has identified this molecule in several new genera. Knowing which genera and species possess neurotoxic components is important to fully understand the repercussions of snakebites, the interaction with prey and predators, and the origin, evolution, and phylogenetic distribution of Crotoxin-like molecules during the evolutionary history of pitvipers. Our study expands current knowledge regarding venom's compositions and function from Mexican pitvipers, providing a comparative venom characterization of major activities in the three Ophryacus species. Additionally, the discovery and characterization of a novel Crotoxin-like molecule, here named Sphenotoxin, in O. sphenophrys, and the detailed protein composition of O. sphenophrys venom supports the hypotheses that Crotoxin-like -β-neurotoxins are more widespread than initially thought.